Ixodes scapularis Tick Saliva Proteins Sequentially Secreted Every 24 h during Blood Feeding. - Tae Kwon Kim; Lucas Tirloni; Antônio F M Pinto; James Moresco; John R Yates; Itabajara da Silva Vaz; Albert Mulenga (Public Library of Science (PLoS), 2016)
Ixodes scapularis is the most medically important tick species and transmits five of the 14 reportable human tick borne disease (TBD) agents in the USA. This study describes LC-MS/MS identification of 582 tick- and 83 rabbit proteins in saliva of I. scapularis ticks that fed for 24, 48, 72, 96, and 120 h, as well as engorged but not detached (BD), and spontaneously detached (SD). The 582 tick proteins include proteases (5.7%), protease inhibitors (7.4%), unknown function proteins (22%), immunity/antimicrobial (2.6%), lipocalin (3.1%), heme/iron binding (2.6%), extracellular matrix/ cell adhesion (2.2%), oxidant metabolism/ detoxification (6%), transporter/ receptor related (3.2%), cytoskeletal (5.5%), and housekeeping-like (39.7%). Notable observations include: (i) tick saliva proteins of unknown function accounting for >33% of total protein content, (ii) 79% of proteases are metalloproteases, (iii) 13% (76/582) of proteins in this study were found in saliva of other tick species and, (iv) ticks apparently selectively inject functionally similar but unique proteins every 24 h, which we speculate is the tick's antigenic variation equivalent strategy to protect important tick feeding functions from host immune system. The host immune responses to proteins present in 24 h I. scapularis saliva will not be effective at later feeding stages. Rabbit proteins identified in our study suggest the tick's strategic use of host proteins to modulate the feeding site. Notably fibrinogen, which is central to blood clotting and wound healing, was detected in high abundance in BD and SD saliva, when the tick is preparing to terminate feeding and detach from the host. A remarkable tick adaptation is that the feeding lesion is completely healed when the tick detaches from the host. Does the tick concentrate fibrinogen at the feeding site to aide in promoting healing of the feeding lesion? Overall, these data provide broad insight into molecular mechanisms regulating different tick feeding phases. These data set the foundation for in depth I. scapularis tick feeding physiology and TBD transmission studies.